주제기록관 운영평가 지표 개발에 관한 연구 - 김은지(Eunji Kim); 한승희(Seunghee Han) (Journal of Records Management & Archives Society of Korea, 2022)
Special subject archives in different fields have been established and the related studies have been constantly made so far, but no evaluation index reflecting the characteristics of the archives has yet been developed. Thus, this study intends to develop a draft of the special subject archive operation evaluation index through literature research and propose the special subject archive operation evaluation index through a Delphi survey. A Delphi survey was conducted thrice, with 10 persons in charge of archiving thematic archives in 5 fields. Finally, a special subject archive operation evaluation index consisting of 4 evaluation categories, 10 evaluation items, and 28 detailed items was proposed. This study is significant because it was the first in Korea to develop and propose an operation evaluation index for special subject archives. 현재까지 여러 분야의 주제기록관이 설립 및 운영되고 관련 연구들도 꾸준히 진행되어왔으나, 주제기록관의 특성을 반영한 평가지표는 아직 개발되지 않은 실정이다. 이에 본 연구에서는 문헌연구를 통해 주제기록관 운영평가 지표(안)을 개발하고, 델파이 조사를 통해 주제기록관 운영평가 지표를 제안하고자 한다. 본 연구에서는 국내 주제기록관 설립과 운영에 대한 연구와 국내·외 기록관리 평가지표 및 국내 유사기관 평가지표를 분석하여 주제기록관 운영평가 지표(안)을 개발하였다. 다음으로, 5개 분야 주제기록관 기록관리 업무 담당자 10명을 대상으로 3차에 걸친 델파이 조사를 실시하여 최종적으로 '주제기록관 운영', '자원관리', '주제기록물 관리', '기록정보서비스'의 4개 평가범주와 10개 평가항목, 28개 세부항목으로 구성된 주제기록관 운영평가 지표를 제안하였다. 본 연구는 국내에서 처음으로 주제기록관의 운영평가 지표를 개발 및 제안하였으며, 본 지표는 주제기록관의 운영에 대한 평가 및 환류를 통해 주제기록관 업무의 전문성과 효율성을 증진시키고, 주제기록관의 기록관리 환경을 개선하며, 운영 및 업무 수행 시 도달하여야 하는 표준적이고 일관적인 기준을 제시한다는 점에서 의의가 있다.